2020
DOI: 10.1515/jcim-2018-0228
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anti-diabetic activity of Citrullus colocynthis pulpy flesh with seeds hydro-ethanolic extract

Abstract: AbstractBackgroundDiabetes is the one of the leading cause of morbidity and mortality. Traditionally phytotherapy is widely being used for diabetes treatment and highly valued. Citrus colocynthis has known anti-diabetic potential. However, anti-diabetic potential of hydro-ethanolic extract of C. colocynthis pulpy flesh with seeds is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The hydro-ethanolic pulpy flesh of C. colocynthis also demonstrated an exceptional anti-hyperglycemic effect in a diabetic rat at the dose rate of 300 mg/kg by decreasing its blood glucose and triglyceride, and cholesterol levels. In vitro testing also showed that C. colocynthis inhibited glucosidase, which is responsible for postprandial hyperglycemia, strongly indicating that it is a potential candidate for a hyperglycemia treatment ( Ghauri et al, 2020 ).…”
Section: Pharmacological Effects Of C Colocynthismentioning
confidence: 99%
“…The hydro-ethanolic pulpy flesh of C. colocynthis also demonstrated an exceptional anti-hyperglycemic effect in a diabetic rat at the dose rate of 300 mg/kg by decreasing its blood glucose and triglyceride, and cholesterol levels. In vitro testing also showed that C. colocynthis inhibited glucosidase, which is responsible for postprandial hyperglycemia, strongly indicating that it is a potential candidate for a hyperglycemia treatment ( Ghauri et al, 2020 ).…”
Section: Pharmacological Effects Of C Colocynthismentioning
confidence: 99%
“…14 C. colocynthis has been used extensively to cure diabetes in folk medicine and contains various biologically active compounds that cause hypoglycaemic effect by inhibiting activity of α-glucosidase. 15 Phenolic compounds (galloylepicatechin) derived from C. colocynthis exhibit antidiabetic potential with no side effects and are attributed as a very low-cost treatment of diabetes and related disorders. 16 The aim of this research was to perform the detailed and indepth phytochemical analysis and to explore the biological potential of bioactive compounds isolated from active fractions of methanolic extract of C. colocynthis.…”
Section: Introductionmentioning
confidence: 99%
“… 14 C. colocynthis has been used extensively to cure diabetes in folk medicine and contains various biologically active compounds that cause hypoglycaemic effect by inhibiting activity of α-glucosidase. 15 Phenolic compounds (galloylepicatechin) derived from C. colocynthis exhibit antidiabetic potential with no side effects and are attributed as a very low-cost treatment of diabetes and related disorders. 16…”
Section: Introductionmentioning
confidence: 99%
“…16 This plant is used in traditional Iranian medicine (TIM) for the treatment of diabetes, abortifacients, epilepsy, jaundice, and asthma due to its many pharmacologic actions. 17,18 Many additional pharmacological qualities have been described, including diuretic, anti-hyperlipidemic, anticancerous, antioxidant, and anti-microbial. 19 In this study, the fruit of C. colocynthis was investigated for its anti-Parkinson's activity using in-vivo biochemical and behavioural experiments in albino Wistar rats, based on the features indicated previously in the literature.…”
Section: Introductionmentioning
confidence: 99%